Bullying among adolescents: does family structure influence the tendency to become a victim of bullying? - Bariyyah, Khairul; Adi Atmoko; Nugraheni Warih Utami; Devy Probowati; Nanda Alfan Kurniawan; Diani Akmalia; Prawira, Sophian Djaka; Wahyuni, Eny Tri (Psikopedagogia, 2025)
Bullying among junior high school students is a significant issue that affects their psychological well-being and academic performance. This study aims to examine the influence of family structure on students' bullying experiences. A causal-comparative research design was applied to investigate the relationship between family structure and bullying tendencies. The population for this study consists of 189,631 junior high school students in Malang City during the odd semester of 2024/2025. The research sample comprises 1,922 junior high school students aged 13-15 years, selected randomly. Data were collected using a valid and reliable family structure questionnaire and bullying scale, with family structure categorized into (1) living with both parents, (2) living with father only, (3) living with mother only, and (4) living with guardians or other family members. Descriptive statistics and one-way ANOVA were used for data analysis. The results showed that family structure did not affect the tendency to become victims of bullying in junior high school students. This suggests that victims of bullying can emerge from any family structure. Based on the findings, it is recommended that the role of the family be strengthened to prevent students from becoming victims of bullying.